The history of Israel ...: translated from the German ... - Ewald, Heinrich (Longmans, Green, 1869)
1. Introduction and preliminary history -- 2. History of Moses and the theocracy -- 3. The rise and splendour of the Hebrew monarchy -- 4. From the disruption of the monarchy to its fall -- 5. The history of Ezra and of the hagiocracy in Israel to the time of Christ -- 6. The life and times of Christ -- 7. The Apostolic age -- 8. The post-Apostolic age.